2021
DOI: 10.3390/metabo11120868
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Metabolites Indicate Differences in High and Low Residual Feed Intake Holstein Dairy Cows

Abstract: Selection for more feed efficient dairy cows is key to improving sustainability and profitability of dairy production; however, underlying mechanisms contributing to individual animal feed efficiency are not fully understood. The objective of this study was to identify circulating metabolites, and pathways associated with those metabolites, that differ between efficient and inefficient Holstein dairy cows using targeted metabolite quantification and untargeted metabolomics. The top and bottom fifteen percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Tryptophan (95%) is degraded by the kynurenine pathway in the liver ( Wu, 2021 ). Martin et al, 2021 utilized untargeted metabolomics for broader research and identified seven amino acids that differed among FE cows, which may also support differences in tissue preference for amino acid utilization. A recent study proposes that adaptive responses alter the purpose of amino acid absorption and the efficiency with which these amino acids are ultimately converted into milk ( Souzaa et al, 2023 ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Tryptophan (95%) is degraded by the kynurenine pathway in the liver ( Wu, 2021 ). Martin et al, 2021 utilized untargeted metabolomics for broader research and identified seven amino acids that differed among FE cows, which may also support differences in tissue preference for amino acid utilization. A recent study proposes that adaptive responses alter the purpose of amino acid absorption and the efficiency with which these amino acids are ultimately converted into milk ( Souzaa et al, 2023 ).…”
Section: Resultsmentioning
confidence: 94%
“…In addition, the declining cost of sequencing and the development of multi-omics techniques have brought large amounts of data and detailed genomic information to genomic selection. Possible loci influencing FE as well as mechanisms of related biological pathways are emerging from genome-wide association studies ( GWAS ) ( Lu et al, 2020 ), transcriptomic studies ( Shi et al, 2018 ), metabolomics studies ( Martin et al, 2021 ), and candidate gene studies ( Delosière et al, 2019 ). These findings could be used to develop precise breeding programs and possibly address genetic antagonism ( Berry et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of profiling metabolites is exploring the impact of metabolism on systemic health by monitoring the production and further metabolism of compounds present in the diet, digesta, and plasma (Seidel et al, 2014). It can also be used to evaluate feed Martin et al, 2021;Artegoitia et al, 2022). Studies have also shown that the heritability of water-soluble compounds such as free amino acids, nucleotides, and sugars in beef was less than 0.30 and varied with animal age (Sakuma et al, 2016).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Of these, metabolism represents nearly half of the variation in RFI in beef cattle [ 9 ]. In dairy cattle, the plasma profile of metabolites differed between more feed efficient (lower RFI) and less feed efficient (higher RFI) cows, most notably in amino acids and acylcarnitines, which indicated differences in amino acid and fatty acid metabolism between the feed efficiency groups [ 10 ]. In a respiration chamber study, early lactation cows with higher energy corrected milk (ECM)/dry matter intake (DMI) had reduced fatty acid oxidation per unit of metabolic body weight (BW) compared with cows with lower ECM/DMI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the postpartum milk production and DMI intake response, and the role choline plays in the liver, choline may influence feed efficiency in mid-lactation. Concentrations of plasma choline were lower and concentrations of plasma betaine were higher in more feed efficient (lower RFI) mid-lactation cows compared with less feed efficient (higher RFI) cows, indicating a potential differential supply or metabolism of choline between animals differing in feed efficiency status [ 10 ]. Given the lower concentrations of choline in more feed efficient animals, it is possible that efficient animals may benefit from supplemental rumen-protected choline.…”
Section: Introductionmentioning
confidence: 99%